Rini, Algoritma Looping - Humdiana Roelly S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2012)
Sometimes in determining the output from an application program having trouble, especially in the looping algorithm, which is usually considered to be complicated. There are a number of variables that must be analyzed along with the algorithm. Another issue is the limitations of human reason to remember all the computational results of all the variables change with the algorithms used in an application program. Under the conditions of these problems, the authors find the design as a method, how easy to analyze the variables in the algorithm and its application program, the authors designed a table that is the purpose of the authors table berinama flowchart analysis combined with the already known standards in the world of computing to analyze each application program. Table analysis to analyze variables along with the documented history of any change of variables while the flowchart to help illustrate the limit and start looping, from any application. Programming language Borland C + + that will use the author in writing this article as a tool to prove the truth of which is the result of computing. The author took a simple application example, the goal is to facilitate the explanation, or convey the concept of the draft results of the analysis table. Experience author in teaching the course Analysis and Design of Algorithms or materials relating to the algorithm, almost all students can apply the analysis is complete the design of the table along with the flowchart in each application program, either simple or difficult applications such as arithmetic applications, sorting, and searching. The result is very satisfactory, meaning that the results are similar to the results of computation, thus the student is in conformity with the logic of computer logic, the results are very satisfactory, pride, and happiness for the writer to deliver the student ketahap. This design can also serve to train and help facilitate the logic in teaching subjects related to the algorithm.